2016
DOI: 10.1186/s40662-015-0032-4
|View full text |Cite
|
Sign up to set email alerts
|

In pursuit of objective dry eye screening clinical techniques

Abstract: Dry eye is a multifactorial, progressive, and chronic disease of the tears and ocular surface. The disease is multi-factorial and has intermittent symptoms. Discomfort, visual disturbance, tear film instability with potential damage to the ocular surface, and increased tear film osmolarity are known associates.Dry eye is a common clinical problem for eye-care providers worldwide and there is a large number of clinical investigative techniques for the evaluation of dry eye. Despite this, however, there is no gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 79 publications
0
17
1
3
Order By: Relevance
“…The lack of reliable diagnosis due to a bedeviled assessment of dry eye syndrome might be secondary to poor diagnostic repeatability, which is manifested as significant false-positive/negative rates, broad range of variability, wide range of sensitivity and specificity, and dependence on clinical conditions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of reliable diagnosis due to a bedeviled assessment of dry eye syndrome might be secondary to poor diagnostic repeatability, which is manifested as significant false-positive/negative rates, broad range of variability, wide range of sensitivity and specificity, and dependence on clinical conditions [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…DED results from either a systemic immunologic disorder known as Sjögren’s syndrome 3 in which there is insufficient production of moisture in the salivary and tear-producing glands, or from the low production or high evaporation of tears caused by other means 4 . Its severity may range from mild/episodic to severe/chronic and the disease is characterized by several symptoms including visual disturbance (blurred and fluctuating vision), foreign-body sensation and eye discomfort, irritation, ocular surface inflammation, redness, excess tearing, and photophobia 5 . DED is treated with a range of proprietary eye drops which contain a variety of active ingredients.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Kanellopoulos et al found a statistical significantly epithelial thickness difference of 6.5 µm between women with dry eye compared with controls. 29 Practical pearls…”
Section: Corneal Evaluationmentioning
confidence: 99%